Konstruksi Realitas Identitas Generasi Milenial (Analisis Semiotika Ferdinand De Saussure Pada Iklan By.U Versi “Sulit Game”) - Ichsan Widi Utomo; Christopher Yudha Erlangga (Jurnal Media Penyiaran, 2022)
Mass media which has now shifted a lot to new media, namely digital media has an in-line development with the identity of the millennial generation, which has characters such as high sensitivity to technology, connected or connected globally and online in terms of communication, so this has an impact on trends in brand or product usage. This research with a qualitative approach was carried out with the aim of knowing the identity of the millennial generation in the signifier and the signified using Ferdinand de Saussure's semiotic analysis. The substance of the Social Construction Theory from Peter L. Berger and Thomas Luckman used in this study shows that there is a social reality built by digital mass media simultaneously in building the character of the millennial generation so that this study shows the results that the millennial generation has differences and changes in patterns in buying and selling. consume the product. The advertisement for the telecommunications provider "By U" version of "Hard Game" featuring Angga Yunanda as a brand ambassador provides a complete illustration of the daily character of the millennial generation who has a high frequency in consuming digital telecommunications media in terms of gaming, vlogging, and communication, where By U provides benefits signal strength and quotas that can facilitate these activities